Reliability and Validity of The Fuzzy Delphi Instrument of Islamic Cognitive Domains Running Head: Reliability and Validity of Islamic Cognitive Domains - Hafizhah Zulkifli; Ahmad Munawar Ismail; Nurul Asiah Fasehah Muhamad; Nur Hanani Hussin; Sri Andayani Mahdi Yusuf (Human Resource Management Academic Research Society, 2024)
Indexed by ERA